Bogdanov-Takens Bifurcation in a Host-Parasitoid Model (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, we study a host-parasitoid model with Holling IIFunctional response, where we focus on a special case: the carrying capacity $K_2$ for parasitoids is equal to a critical value $\frac{r_1}{η}$. It is shown that the model can undergo Bogdanov-Takens bifurcation. The approximate expressionsfor saddle-node, Homoclinic and Hopf bifurcation curves are calculated. Numerical simulations, including bifurcation diagrams and corresponding phaseportraits, are also given to illustrate the theoretical results.